A study on service quality and tourist loyalty: A case study of the Sarawak Tourism Board, Malaysia - Robinson, Kiong (2010)
The primary objectives of this study are to examine the relationship between service quality and service loyalty in the hotel industry by using SERVQUAL and 4 battery of service loyalty. Towards that end, a questionnaire methodology was chosen for this study. Overall, the results of the study seem to indicate that services quality perception is positively related to service loyalty. In other words tourist that perceive service quality as high are more likely to be loyal. A further examination on the individual level concludes that the entire service dimensions are positively related in a positive way with the individual 4 items of loyalty. Meanwhile the 5 dimension is proven to be positively related to the 4 items of loyalty.